Opioid use, pain intensity, age, and sleep architecture in patients with fibromyalgia and insomnia. Issue 9 (September 2019) - Curtis, Ashley F.; Miller, Mary Beth; Rathinakumar, Himangshu; Robinson, Michael; Staud, Roland; Berry, Richard B.; McCrae, Christina S.
Abstract : Abstract: Opioid use and sleep disruption are prevalent in fibromyalgia. Yet, the effects of opioids on physiological sleep in fibromyalgia are unclear. This study assessed associations between opioid use/dosage and polysomnographically assessed sleep in patients with fibromyalgia and insomnia (FMI) and examined moderating effects of age and pain. Participants (N = 193, Mage = 51.7, SD = 11.8, range = 18-77) with FMI completed ambulatory polysomnography and 14 daily diaries. Multiple regression determined whether commonly prescribed oral opioid use or dosage (among users) independently predicted or interacted with age/pain intensity to predict sleep, controlling for sleep medication use and apnea hypopnea index. Opioid use predicted greater %stage 2 and lower %slow-wave sleep (%SWS). Opioid use interacted with age to predict greater sleep onset latency (SOL) in middle-aged/older adults. Among opioid users (n = 65, ∼3 years usage), opioid dose (measured in lowest recommended dosage) interacted with age to predict SOL and sleep efficiency; specifically, higher dosage predicted longer SOL and lower sleep efficiency for older, but not middle-aged/younger adults. Opioid dose interacted with pain to predict %SWS and arousal index. Specifically, higher dosage predicted reduced %SWS and higher arousal index for individuals with lower pain, increased %SWS for individuals with higher pain, and did not predict %SWS for patients with average pain. Opioid use/dosage did not predict wake after sleep onset, total sleep time, %stage 1 or %rapid eye movement sleep. Opioid use prompts changes in sleep architecture among individuals with FMI, increasing lighter sleep and reducing SWS. Sleep disruption is exacerbated at higher opioid doses in older adults and patients with low pain. Abstract : Opioid use increases lighter sleep/reduces deep sleep in patients with chronic widespread pain. Higher doses exacerbate disruption in older patients and patients with low pain.